2015
DOI: 10.1158/1078-0432.ccr-14-3374
|View full text |Cite
|
Sign up to set email alerts
|

Immune Recovery after Allogeneic Hematopoietic Stem Cell Transplantation Following Flu-TBI versus TLI-ATG Conditioning

Abstract: Purpose: A conditioning regimen for allogeneic hematopoietic cell transplantation (HCT) combining total lymphoid irradiation (TLI) plus anti-thymocyte globulin (ATG) has been developed to induce graft-versus-tumor effects without graft-versus-host disease (GVHD).Experimental Design: We compared immune recovery in 53 patients included in a phase II randomized study comparing nonmyeloablative HCT following either fludarabine plus 2 Gy total body irradiation (TBI arm, n ¼ 28) or 8 Gy TLI plus ATG (TLI arm, n ¼ 25… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
27
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 53 publications
(78 reference statements)
4
27
0
Order By: Relevance
“…The experiments were performed according to the manufacturer's recommendation, and results were acquired on Bio-Plex System and analyzed with Bio-Plex Manager Software 4.0 (Biorad Laboratories) as previously reported (41). …”
Section: Methodsmentioning
confidence: 99%
“…The experiments were performed according to the manufacturer's recommendation, and results were acquired on Bio-Plex System and analyzed with Bio-Plex Manager Software 4.0 (Biorad Laboratories) as previously reported (41). …”
Section: Methodsmentioning
confidence: 99%
“…Peripheral blood mononuclear cells were phenotyped on days 30, 90 and 180 using 4-color flow cytometry after treatment with a red blood cell lyzing solution as described [25]. Tregs as previously reported [26].…”
Section: Peripheral Blood Lymphocyte Immunophenotyping and Cd4 Phenotmentioning
confidence: 99%
“…[29,61] Several studies have reported that ATG more specifically induces profound and prolonged depletion in the naive compartment of T cells. [46,62] Three phase III randomized trials have reported that pre-transplant ATG successfully decreased the incidence of both a-and cGVHD without increasing the risk of relapse after myeloablative alloHSCT with related [63] or unrelated PBSC. [64,65] In RIC setting, the role of ATG has not been formally established yet.…”
Section: T-cell Depleting Approachesmentioning
confidence: 99%